efficacy of measles vaccine in study among primary school children during measles outbreak in Iraqi for the year 2004 - Alizi, sana a Muhammed Hussian; Alhamadani, faisal Ghazi Nasser (Journal of the Faculty of Medicine Baghdad, 2008)
Background: progress towards the control of measles require a national capacity to measure program affectiveness.